2021
DOI: 10.1002/sus2.10
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in thick‐film organic photovoltaic devices: Materials, devices, and processing

Abstract: A successful transfer of organic photovoltaic technologies from lab to fab has to overcome a range of critical challenges such as developing high-mobility light-harvesting materials, minimizing the upscaling losses, designing advanced solar modules, controlling film quality, decreasing overall cost, and extending long-operation lifetime. To realize large-area devices toward practical applications, much effort has been devoted to understanding the fundamental mechanism of how molecular structures, device archit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 141 publications
(357 reference statements)
0
72
0
Order By: Relevance
“…Bulk heterojunction (BHJ) polymer solar cells (PSCs), as one of the most promising next-generation photovoltaic devices [1,2], have attracted considerable interest due to their versatile advantages of lightweight, flexibility, and ability to manufacture low-cost large-area devices [3,4]. In particular, PSCs with a incorporating conjugated polymer donor and a non-fullerene small-molecule acceptor (NFSMA) as an active layer have achieved significant advances due to continuous innovations in the development of efficient photovoltaic materials [5][6][7] and interface buffer layer materials [8], as well as the optimization of active layer mor-phology [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Bulk heterojunction (BHJ) polymer solar cells (PSCs), as one of the most promising next-generation photovoltaic devices [1,2], have attracted considerable interest due to their versatile advantages of lightweight, flexibility, and ability to manufacture low-cost large-area devices [3,4]. In particular, PSCs with a incorporating conjugated polymer donor and a non-fullerene small-molecule acceptor (NFSMA) as an active layer have achieved significant advances due to continuous innovations in the development of efficient photovoltaic materials [5][6][7] and interface buffer layer materials [8], as well as the optimization of active layer mor-phology [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Organic solar cells (OSCs) have versatile features, such as semitransparency, light weight, and flexibility, endowing them with great potential for applications in flexible solar panels and building-integrated photovoltaics. [1][2][3][4][5][6][7][8] The active layer with bulk heterojunction (BHJ) microstructure of OSCs is usually formed by a polymer donor and a molecular acceptor. [9] Compared with conventionally used fullerene-derived electron acceptors, nonfullerene electron acceptors (NFEAs) show significantly improved photovoltaic performance and great potential for applications.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid technological and economic development of our societies, an intelligent industry centered on new materials and new equipments is gradually rising all around the world. 1,2 Due to the ability to realize the mutual conversion of mechanical energy and electrical energy, [3][4][5] piezoelectric materials have aroused great interest in practical applications, and are widely used in sensing, energy storage, electronics and other elds. 6,7 For example, Li et al 8 demonstrated a non-lead (ZnO) piezoelectric device powered by heart movement.…”
Section: Introductionmentioning
confidence: 99%